Involving rural youth in agroecological nature-positive farming and culinary agri-ecotourism for sustainable development: The Indian scenario - Rana, Jai Chand; Bisht, Ishwari Singh; Mathur, Prem; Fadda, Carlo; Mittra, Sarika; Ahlawat, Sudhir Pal; Vishwakarma, Harinder; Yadav, Rashmi (MDPI, 2024)
Industrial food systems produce most of the food that we consume globally today. But many observers acknowledge that industrial agriculture cannot be sustained in the long run. As such, agroecological practices that encourage sustainable farming practices with a focus on local markets and the local economy are being promoted more and more to change the way food systems work. The current research examines how rural youth can best be involved in food system transformation as a potential agent of change. The research considers the potential of payments for environmental services (PESs) in the study area. The economic potential of gastronomic agri-ecotourism in various traditional agricultural landscapes of different agroecosystems of India has also been investigated. Gastronomic agri-ecotourism has the potential to provide economic benefits to traditional agricultural landscapes and agroecosystems while also promoting sustainable tourism practices. The results of an exploratory study on rural youth participation in nature-friendly agroecological regenerative farming and culinary agri-ecotourism initiatives are presented in this paper in an effort to increase the sustainability of conventional farming and food systems. This study, which was carried out in four different agroecological settings in India, sheds light on the opportunities and problems faced by rural youth, as well as their motivations.